(untitled) (Indian Journal of Arid Horticulture, 2017)
The field investigation was conducted to study the effect of fertility level and biofertilizers on seed yield and quality of cluster bean. On the basis of investigation, it was concluded that application of fertilizer level at 25:50 kg N:P/ha (F3) found to be beneficial in recording seed yield and quality of cluster bean. As regard to the biofertilizers, application of rhizobium and PSB in combination was found to be beneficial in producing highest seed yield, straw yield and improved its quality i.e. gum content and viscosity profile as compared to rest of treatments. The interaction effect of fertility level and biofertilisers was significant for straw yield and biological yield.